2013
DOI: 10.1016/j.envpol.2013.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Expression of zinc and cadmium responsive genes in leaves of willow (Salix caprea L.) genotypes with different accumulation characteristics

Abstract: Salix caprea is well suited for phytoextraction strategies. In a previous survey we showed that genetically distinct S. caprea plants isolated from metal-polluted and unpolluted sites differed in their zinc (Zn) and cadmium (Cd) tolerance and accumulation abilities. To determine the molecular basis of this difference we examined putative homologues of genes involved in heavy metal responses and identified over 200 new candidates with a suppression subtractive hybridization (SSH) screen. Quantitative expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Hybrid aspen ( P. trichocarpa × deltoides ) PtdMT2B conferred Cd tolerance to a Cd sensitive yeast strain (Kohler et al, 2004), and the MT2B expression levels of P. tremula × tremuloides correlated with foliar Zn and Cd concentrations on metal contaminated soil (Hassinen et al, 2009). Konlechner et al (2013) also reported induced metallothionein expression might constitute a general metal response in S. caprea leaves allowing higher Zn and Cd uptake. S. integra could accumulate 90–288 mg Cd Kg −1 dry weight in their leaves, however, molecular mechanisms underlying the high accumulation of Cd in leaves were still uncovered.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Hybrid aspen ( P. trichocarpa × deltoides ) PtdMT2B conferred Cd tolerance to a Cd sensitive yeast strain (Kohler et al, 2004), and the MT2B expression levels of P. tremula × tremuloides correlated with foliar Zn and Cd concentrations on metal contaminated soil (Hassinen et al, 2009). Konlechner et al (2013) also reported induced metallothionein expression might constitute a general metal response in S. caprea leaves allowing higher Zn and Cd uptake. S. integra could accumulate 90–288 mg Cd Kg −1 dry weight in their leaves, however, molecular mechanisms underlying the high accumulation of Cd in leaves were still uncovered.…”
Section: Discussionmentioning
confidence: 95%
“…Although fast growing woody plants have been widely used for cleaning up HM contaminated soils, limited information is available about the physiological and molecular mechanisms of HM tolerance and detoxification in woody plants (Konlechner et al, 2013; Luo et al, 2016). To date, most of genes involving in HM uptake, transport, sequestration, and detoxification in woody plants were restricted to Populus (Marmiroli et al, 2011; Luo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several trials have investigated the gene expression or transcriptomic response of willow, and similar crops, to a number of inorganic contaminants applied in isolation, such as: chromium [ 17 ], copper [ 18 ], zinc [ 19 ] and cadmium [ 20 ]. Little research, however, has investigated the transcriptomic response of woody crops to organic contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Physiological and biochemical properties have been characterized in S. matsudana 3435. Meanwhile, some key genes have been identified to regulate stress response factors in stressed plants at the molecular level363738. Understanding the expression patterns of key stress response genes will help elucidate the mechanisms involved in various stresses of S. matsudana .…”
mentioning
confidence: 99%